مدى توافر العوامل المؤثرة في فاعلية المراجعة الحكومية الخارجية "دراسة ميدانية على ديوان المحاسبة الليبي" - الشيخي , آمال سعد; معيوف , خديجة علي; الشكري, عائشة سالم (Scientific Journal of University of Benghazi, 2023)
The study aimed to define the influencing factors in the effectiveness of government audit issued by the Institute of Internal Auditors (IIA), and to find out the availability of these factors in the external audit practiced by the Libyan Audit Bureau. The study relied on the analytical descriptive approach, a questionnaire was designed and distributed to a sample of 94 external auditors at the Libyan Audit Bureau, in using the descriptive statistics and the One Sample T-Test for analyzing the collected primary data. The results of the study showed that the influencing factors in the effectiveness of the government audit issued by (IIA) are available in the external auditing practiced by the Libyan Audit Bureau in varying degrees. The objective staff was the most influencing factor available at a very high degree, followed respectively by the unrestricted access, the competent staff, adherence to the professional audit standards, the formal mandate, the organizational independence, and the competent leadership all of these factors were available at high degrees, while the sufficient funding and the stakeholder support were the least influencing factors available and at a moderate degree. The study recommended the necessity for providing sufficient funding for the Libyan Audit Bureau to perform its tasks in better way, and work to provide Stakeholder support to increase its controlling efficiency. The study also recommended spreading public awareness of the importance of the controlling role of the Bureau in order to preserve the public money and combating the corruption.